Sociocultural strategies for stress reduction among hospitality workers in developing contexts: the case of Zimbabwean chefs - Mkono, Muchazondida (Cognizant Communication Corporation, 2021)
In the media, the chef profession is portrayed as exciting and glamorous. However, research on the ground reveals that the job is characterized by high levels of stress and burnout, resulting from long and unsocial working hours, poor remuneration, close and direct supervision, and few career advancement opportunities, among other factors. Although the problem of job stress and burnout in hospitality jobs is well recognized in the literature, most of the empirical research has largely overlooked African countries. This study is an attempt to investigate sociocultural strategies for coping with stress and burnout in a developing country context, and to analyze these interpretively within the relevant sociocultural framework. Semistructured interviews were carried out with 23 hotel chefs in the resort town of Victoria Falls, Zimbabwe. The research concludes that any effective strategy for dealing with stress in the workplace can only be successful to the extent that it takes into account relevant sociocultural dynamics.